Strategic thinking and its impact on strategic leadership through the mediation of forward-looking leadership: An exploratory analytical study of a number of academic leaders at Al-Mustansiriya University (International Journal of Financial, Administrative and Economic Sciences, 2026)
Through this research, the researcher aims to highlight the concepts of (strategic thinking) with its dimensions (visionary thinking, synthetic thinking, creative thinking, reflective skills, systems thinking), and forward-looking leadership with its dimensions (forward-looking thinking, forward-looking vision, building a forward-looking culture), and strategic leadership with its dimensions (proactivity, innovation, strategic vision, and strategic flexibility), given the importance of these concepts collectively in organizations today, especially educational organizations, due to the significant and rapid changes in teaching methods and approaches, and the pursuit by most educational organizations of leadership in the field of education. The research began with the question: Does strategic thinking have an impact on strategic leadership? Does this effect increase through the mediation of forward-looking leadership? The researcher chose a number of colleges at Al-Mustansiriya University to be the applied field of the research. The researcher chose a purposive sample of (74) academic leaders in these colleges at the level of college dean, assistants, and heads of departments. (70) questionnaires were retrieved, and the hypotheses were examined using the statistical programs (SPSS v28) using a set of statistical methods, including (Cronbach's alpha reliability coefficient, construct validity, arithmetic mean, standard deviation, relative importance, linear regression coefficient). The most prominent result of the research was that the effect of strategic thinking on strategic leadership is not achieved with maximum effectiveness directly, but rather increases more when forward-looking leadership is available, as the indirect effect through forward-looking leadership was stronger than the direct effect, which confirms that forward-looking leadership represents the organizational mechanism that transforms the outputs of strategic thinking into actual entrepreneurial practices within the university.
Keywords: Strategic Thinking; Strategic Leadership; Forward-Looking Leadership